Dioscorea longipedicellata (Dioscoreaceae), a new species from the Indian subcontinent - Hoque, Akramul; Lakshminarasimhan, Pakshirajan; Maity, Debabrata (Phytotaxa, 2018)
A new species of Dioscorea, viz., D. longipedicellata is described and illustrated based on collections from northeast India and northwest Bangladesh. The new species is closely allied to D. kamoonensis and D. pentaphylla. D. longipedicellata can be diagnosed by its glabrous stem, glabrous membranous lamina, pedicellate male flowers, funnel-shaped, fleshy prominent pedicels, glabrous bract situated at the base of pedicel directly on rachis and membranous, glabrous tepals.